2015
DOI: 10.1080/08870446.2015.1034720
|View full text |Cite
|
Sign up to set email alerts
|

Depression and marital status determine the 10-year (2004–2014) prognosis in patients with acute coronary syndrome: The GREECS study

Abstract: The present study highlights the important role of depression in the context of marital relationships among ACS patients. Secondary public health care intervention programmes are needed to improve patient outcomes and minimise disease burden in clinical and community setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
2
8
0
1
Order By: Relevance
“…CVD than those without depression [24]. The results of this study are consistent with those of several studies showing that depression and anxiety among people with other diseases predicted CVD [25][26][27].…”
Section: E P U B a H E A D O F P R I N Tsupporting
confidence: 92%
“…CVD than those without depression [24]. The results of this study are consistent with those of several studies showing that depression and anxiety among people with other diseases predicted CVD [25][26][27].…”
Section: E P U B a H E A D O F P R I N Tsupporting
confidence: 92%
“…25 The general log-linear model also showed that there is an association between the variable marital status and MDD conditioned to gender. What can be inferred from this is that this association pertained to the unmarried and females, who, as aforementioned, showed a greater tendency to MDD than married persons and males.…”
Section: Discussionmentioning
confidence: 91%
“…The GREECS study found similar associations, amplified by depression severity, between marital status and recurrent acute coronary syndrome in approximately 2000 patients. 26 Although some studies suggest that marital status affects cardiac rehabilitation programme attendance and physical activity in secondary prevention, 27,28 possible underlying effects on the association as well as causality remain unclear. The gender interaction observed in the current study for the association between unmarried status and the outcome may indicate that men, to a larger extent than women, are dependent on a spouse to adhere to treatment.…”
Section: Discussionmentioning
confidence: 99%